MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN KE SEKOLAH DAN MENGAJAR DI KELAS MELALUI PENERAPAN “REWARD AND PUNISHMENT” - Azmi Azmi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The teacher is a professional educator with the main task of educating, teaching, guiding, directing, training, evaluating and evaluating students in the formal education pathway, at the level of primary and secondary education. Therefore, increasing teacher discipline in carrying out tasks is very important in the smoothness and success of the school in achieving its objectives. However, based on preliminary observations, researchers still find teachers who are late to school for various reasons and there are still teachers who are late in class. Overcoming this problem researchers use the reward and punishment method. The results showed, in the first cycle, the average total of teachers who were late for school was 59.9% and the average teacher who was late for class in the teaching and learning process was 79.9%. after the second cycle, the results of observations of the discipline of teachers coming to school and attending classes showed a large increase, this was evidenced by the increased discipline of teachers in terms of attending school and being present on time in the teaching and learning process. The average value of teachers who attend school late in the second cycle dropped to 19.9% and the average value of teachers who were late to attend the class dropped to 26.6%. this result proves that by applying the reward and punishment model it can improve teacher discipline.